2007
DOI: 10.1038/sj.ijo.0803656
|View full text |Cite
|
Sign up to set email alerts
|

Defined weight expectations in overweight women: anthropometrical, psychological and eating behavioral correlates

Abstract: Objective: To examine associations between defined weight expectations and anthropometric profile and to identify psychological and eating behavioral factors that characterize women having more realistic weight expectations. Methods: A nonrandom sample of 154 overweight/obese women completed the 'Goals and Relative Weight Questionnaire', which assessed four weight expectations: (1) dream weight (whatever wanted to weight); (2) happy weight (would be happy to achieve); (3) acceptable weight (could accept even i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 39 publications
2
28
0
4
Order By: Relevance
“…In general, patients tend to have unrealistic expectations with respect to the outcome of bariatric surgery [18]. In nonsurgical weight loss interventions, these unrealistic expectations have been shown to be linked to higher attrition [19], lower satisfaction [12], and less healthy psychological and eating behavior characteristics [13] but not to maintenance of weight loss [12,17]. In the current study, the prognostic effects of expectations, satisfaction and unfulfilled expectations are disentangled.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In general, patients tend to have unrealistic expectations with respect to the outcome of bariatric surgery [18]. In nonsurgical weight loss interventions, these unrealistic expectations have been shown to be linked to higher attrition [19], lower satisfaction [12], and less healthy psychological and eating behavior characteristics [13] but not to maintenance of weight loss [12,17]. In the current study, the prognostic effects of expectations, satisfaction and unfulfilled expectations are disentangled.…”
Section: Introductionmentioning
confidence: 71%
“…These theories, as well as the observation that positive outcome expectations predict the outcome of nonsurgical weight loss interventions [12][13][14], led to our first hypothesis that favorable preoperative expectations with respect to the psychosocial outcomes after LAGB would promote postoperative weight loss at 1 year. As shown in another study on bariatric surgery patients [15], the hypothesis was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historicamente está identificada e relacionada à fase da adolescência e aos distúrbios alimentares, mas estudos têm identificado grandes prevalências de insatisfação com o corpo também em idosos, principalmente nas mulheres [5][6][7] . A percepção da imagem corporal e os sentimentos de insatisfação que podem influenciar negativamente a vida geral das pessoas, seu desempenho profissional e mesmo o relacionamento interpessoal estão associados a situações de sobrepeso e obesidade 8,9 . Apesar disso, a insatisfação com o corpo também vem sendo identificada em indivíduos com estado nutricional dentro dos padrões de normalidade 10 , remetendo a uma grande pressão social e da mídia por determinados padrões de corpo e até mesmo problemas para identificar (e aceitar) sua própria imagem corporal.…”
Section: Introductionunclassified
“…10 Possíveis distúrbios na percepção do corpo podem ser investigados com base na relação da percepção da imagem corporal com os índices e as medidas antropométricas, estando associados principalmente ao sobrepeso e obesidade; no entanto, já se observa insatisfação com o corpo em idosos eutróficos, remetendo à pressão social e da mídia por padrões de beleza definidos. 11,12 Portanto, conhecer a relação que o idoso mantém com seu corpo e as implicações sobre sua autoestima e autoimagem é fundamental para que os profissionais de saúde atuem de forma multiprofissional e considerem em suas práticas todos os aspectos que envolvam a saúde do indivíduo, sejam físicos, psicológicos, emocionais, mentais, entre outros, englobandoos de maneira holística. 13 Assim, este estudo teve por objetivo verificar a relação entre o índice de massa corpórea, a autoestima e a autoimagem corporal de idosas participantes de grupos da terceira idade.…”
unclassified